Sistematización de la Experiencia de Montaje Conjunto “Esto Es Vida” (2016)
The process begins with the population made up of people older people, which was made up of 12 women with whom they worked on different workshops, later in the first half of 2015, the staging was carried out of the joint production “This is Life” at the Antonio Nariño University. At the time of work with this population, different workshops were held to obtain a diagnosis and In this way, develop an appropriate work plan for the management of the group, step Next, information was sought that would explain what the bibliographic support would be for each of the classes and workshops; which was not easy to find, since the literature of texts applied to dance in the elderly, is scarce and is not found in the state of art, for this reason another path was sought and this was to investigate with the masters dance experts from the program, how they would approach through their experience as teachers and dance professionals, an appropriate methodology for this population especially.